Alternative housing for faculty and students in Bulacan State University - Villanueva, Eva Maria Capulong (College of Architecture, University of the Philippines Diliman, 2008)
This thesis studies architectural strategies responsive to the needs of students for decent and affordable on-campus accommodations which are integrated into faculty housing units. The main goal is to address the feasibility of creating a "homelike" environment which supportive of the development of the students without compromising the living requirements of the faculty members. By focusing on the recursive patterns of behavior within existing similar residential setups and how they are connected with the spatial structure, the existing student dormitories around Bulacan State University (BSU) were studied and how their conditions affect the behavior choices of the residents.